758 Unique Case of Recurrent Non-Neutropenic Typhlitis. (19th August 2022) - Sahni, D; Stockdale, H; Leiberman, D; Stevenson, R
Abstract: Tacrolimus is an important component of the immunosuppressive regime used after solid organ transplantation. It is known to predispose patients to typhlitis also known as neutropenic enterocolitis, which presents with the characteristic triad of abdominal pain, fever, and neutropenia. A 66-year-old lady was referred with vomiting, abdominal pain, and passage of blood per ileostomy. The patient had an extensive medical history including a panproctocolectomy for Crohn's disease, cholecystectomy and a liver transplant. Her immunosuppressive regime included prednisolone, azathioprine, and tacrolimus. Based on her presentation, a presumptive diagnosis of ischemic bowel was made, and non-contrast (due to AKI) CT scan demonstrated evidence of intramural gas with marked mesenteric and portal venous gas. The decision was made to proceed to laparotomy, the findings of which included dense adhesions but with normal healthy small bowel. After several investigations, it was concluded that her symptoms were caused by typhlitis secondary to her tacrolimus therapy. In 2020, the patient presented with similar symptoms. She was able to undergo a contrast-enhanced CT scan during this episode as she had presented early with preserved renal function. Her radiological findings were similar to the previous episode. However, owing to her known past history, she was managed conservatively. To the authors knowledge, no similar cases have been reported so far, which makes this case unique and makes a strong motion for the clinicians to maintain a high suspicion for typhlitis inmmunocompromised patients, even in absence of classical feature of neutropenia